USING COLLABORATIVE LEARNING TECHNOLOGIES IN DRAWING LESSONS - Boburmirzo Bakhodir ugli Kokiyev (Galaxy International Interdisciplinary Research Journal, 2022)
The article contains recommendations for future teachers of fine arts and drawing on the use of new pedagogical technologies in the organization of lessons and their application to the lesson process.